Novel porous scaffolds for tissue engineering cartilage - Unsworth, Jennifer (2004)
Damage to cartilage, caused either by disease or injury, affects a large number of people worldwide, severely reducing the patient's quality of life and generating a huge burden on healthcare systems. The limited success of treatment options such as tissue grafts has been the driving force behind much research into tissue engineering strategies for cartilage repair. One of the challenges associated with tissue engineering cartilage is that of generating constructs of clinically relevant sizes since the formation of a crust of tissue at the scaffold periphery restricts the supply of nutrients to the growing tissue. The hypothesis of this thesis was that a tissue engineering system incorporating scaffolds containing both random and anisotropic porosity and a novel flow perfusion bioreactor system would facilitate in vitro tissue formation by enhancing the supply of nutrients to the growing construct. This hypothesis was examined using cartilage as a model tissue. It was shown that scaffolds combining both random and anisotropic porosity (sparse knit scaffolds) had improved flow properties compared to scaffolds containing random porosity alone (needled felt scaffolds). Following studies to characterise the scaffolds and to determine the appropriate conditions for seeding cells into the scaffolds, cartilage formation within the different scaffolds was assessed over a four week culture period. It was found that the flow perfusion system was not as favourable for in vitro cartilage formation as either the commercially available Rotary Cell Culture System (RCCS) or static culture. One of the sparse knit scaffolds (sparse knit 4) and the needled felt were further compared for cartilage formation over an eight week culture period, using static and RCCS culture. With respect to collagen and glycosaminoglycan (GAG) production, cartilage constructs generated from the two scaffold systems were similar. Following static culture it was found that more viable cells were present at the centre of sparse knit 4 scaffolds than needled felt scaffolds. It was therefore concluded that scaffolds combining random and anisotropic porosity were advantageous for culturing tissues in environments where nutrient supply was reliant on diffusion alone.